2022
DOI: 10.1177/00224871221105799
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Teacher Research Involvement? Factoring in Language Teachers’ Big Five Personality Traits and Motivation to Conduct Research

Abstract: The important role of individual differences in affecting teachers’ involvement in and professional development through research has received little systematic attention in theoretical discussions and empirical studies on teacher research. Therefore, relying on the available literature and our proposed theoretical models, we investigated the possible links among language teachers’ Big Five personality traits, motivation to conduct research (through self-determination theory’s intrinsic and extrinsic motivation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…A second limitation, informed by Bahrami and Hosseini (2023), was that teachers’ underlying personality traits may have affected their motivation to participate but were not explored. The motivation to engage in practitioner inquiry focused on the instruction of difficult topics could vary by individual, with already-motivated individuals most likely to participate.…”
Section: Limitations and Implicationsmentioning
confidence: 99%
“…A second limitation, informed by Bahrami and Hosseini (2023), was that teachers’ underlying personality traits may have affected their motivation to participate but were not explored. The motivation to engage in practitioner inquiry focused on the instruction of difficult topics could vary by individual, with already-motivated individuals most likely to participate.…”
Section: Limitations and Implicationsmentioning
confidence: 99%
“…This means that the effects of PD, whether formal or informal, hinge not only on its form, quality, frequency, and availability but also on language educators' readiness to avail themselves of such opportunities and their response to them. Thus, whether different forms of PD will have a bearing on instructional practices depends on an interplay of cognitive, affective, and motivational processes as well as a range of ID characteristics (Bahrami & Hosseini, 2023;Korthagen, 2017;Schutz & Zembylas, 2009;Zhang et al, 2021). One attribute that may be a pivotal ingredient of PD processes and mitigate their outcomes is language teacher professional curiosity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kashdan and Silvia (2009, p. 370) note that "there are important social and institutional moderating variables" which require consideration in order to "understand the conditions leading to favorable and unfavorable" contexts for curiosity-driven behaviors. Ashcroft et al (2020) point to the importance of a culture characterized by "psychological safety" as being key to fostering curiosity. In other words, people need to feel safe and confident in their contexts to explore and be curious.…”
Section: Agency and Socio-cultural Contextsmentioning
confidence: 99%
“…Research has reported significant relationships between extroversion and neuroticism, on the one hand, and job stress [ 40 ] or wellbeing, on the other [ 41 ], as well as the moderating role of extraversion and neuroticism on work-related outcomes [ 42 ]. Recent studies continue applying personality traits as relevant individual differences associated to motivation to teach [ 43 ], research involvement [ 44 ]or academic performance among Chinese teachers [ 45 ].…”
Section: Literature Reviewmentioning
confidence: 99%